Hatching Performance of Indonesian Native Chicken Supplemented by L-Glutamine at Different Days of Incubation - Muhammad Rachman Hakim; D. Daryatmo; Djoni Prawira Rahardja; Wempie Pakiding (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2019)
The present study aimed to determine the hatching performance of native chicken subjected to the supplementation of L-Glutamine at different days of incubation. A total of 240 fertilized eggs native chicken eggs with an initial weight of 48.85 ± 3.3 g, were subjected to injection of glutamine on the 7th, 9th and 11th day of incubation, while the control group received no injection. A total of 1.5% glutamine was dissolved in 0.5 mL of saline solution and injected at the pointed part of the egg with the target into the albumen. Hatchability, incubation time, and chick weight at hatch were determined during the study. The hatchability of native chicken treated with an injection of glutamine amino acid on different incubation days was still lower than of the control group. However, hatches were generally more substantial in size. The incubation time of the injected chicks was longer than that of the control. Chicks from injected of glutamine on the 11th day of incubation were 12.31% heavier than controls and did not differ from injections on the day 7th and 9th of incubation. The results of this study indicated that the administration of glutamine to obtain more massive chicks at the time of hatching could be conducted on the 7th, 9th and 11th days of incubation, even with lower hatchability.